2013
DOI: 10.1037/a0031991
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trends and individual differences in brain systems involved in intertemporal choice during adolescence.

Abstract: This study used functional magnetic resonance imaging (fMRI) to examine the neural systems activated during an intertemporal choice task in a group of 14- to 19-year-old adolescents, as well as the relationship of such activation patterns to individual differences in the self-reported ability to engage in nonimmediate thinking (i.e., less impulsive and more future-oriented thoughts and action). With increasing age, there was greater differentiation between patterns of brain activity for immediate versus future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…4 According to this model, three different brain systems affect individual differences in intertemporal choice: The first supports the representation of the subjective value of the options; the second supports self-control, conflict resolution, and strategy adaptation; the third is involved in imagining the future or future outcomes. As stressed by Banich et al (2013), all these systems "are undergoing important developmental changes during adolescence" (p. 417).…”
Section: The Present Workmentioning
confidence: 99%
See 2 more Smart Citations
“…4 According to this model, three different brain systems affect individual differences in intertemporal choice: The first supports the representation of the subjective value of the options; the second supports self-control, conflict resolution, and strategy adaptation; the third is involved in imagining the future or future outcomes. As stressed by Banich et al (2013), all these systems "are undergoing important developmental changes during adolescence" (p. 417).…”
Section: The Present Workmentioning
confidence: 99%
“…According to Steinberg et al (2009), a preference for immediate rewards and a lower sensitivity to the longer term consequences of one's present behavior "may be more strongly related to arousal of the socioemotional network 3 than to immaturity in cognitive control" (p. 40). More recently, building on the model proposed by Peters and Büchel (2010), 4 Banich et al (2013) examined the role of developmental trends and individual differences in brain systems in intertemporal choice in a group of 14-to 19-year-old adolescents. Relevant to the current work, Banich et al (2013) demonstrated that age differences in intertemporal decision-making were related to the cognitive control system, and mainly, even if not exclusively, involved frontal regions" (p. 425).…”
Section: The Present Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cross-sectional studies (e.g., Green et al 1994;Harrison et al 2002;Steinberg et al 2009;Yoon et al 2007) have demonstrated that younger individuals discount delayed rewards more steeply than older individuals, and they have the tendency to choose small immediate rewards, rather than larger delayed rewards declines with age (e.g., Olson et al 2007;Scheres et al 2006;Steinberg et al 2009; see Albert and Steinberg [2011] for a review). This is probably due to individual difference factors (such as future orientation and impulsivity), cognitive functioning (such as the ability to imagine and experience pleasure or pain in advance of future events), and the maturation of brain system during adolescence (Banich et al 2013). A recent study by Anokhin, Golosheykin, and Mulligan (2015) demonstrated that, in spite of the presence of systematic age-related changes from age 16 to 18 years, individual differences in delay discounting showed considerable stability over this period.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Banich et al (2013) examined the neural systems activated during the process of intertemporal choices and its association with non-immediate thinking (NIT), in two groups of adolescents (one group in the initial phase of adolescence, between the ages of 14 and 16, and another at the final phase of adolescence, from 17 to 19 years old). They observed different patterns of brain activity in immediate vs. future choices involving three distinct brain systems, namely, cognitive control (inferior/middle/superior frontal gyrus and lateral frontal pole), evaluation (brain stem and ventral tegmental area), and prospection (parahippocampal gyrus).…”
Section: Agementioning
confidence: 99%